PENERAPAN MODEL PEMBELAJARAN KOOPERATIF TIPE TWO STAY TWO STRAY (TSTS) UNTUK MENINGKATKAN HASIL BELAJAR IPS SISWA KELAS IV SD NEGERI 007 BAGAN JAWA - Rubiyah '; Otang Kurniaman; Zariul Antosa (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2017)
Abstract : This research is motivated by the lack of IPS student learning outcomes, with an average grade of 70. Among the students of 16 people only 6 students who completed KKM with classical completeness reached 37.50%. This research is a classroom action research (CAR) conducted aims to improve learning outcomes IPS Elementary School fourth grade students 007 Bagan Jawa by implementing cooperative learning model Two Stay Two Stray (TSTS). Data collection instrument in this paper is a sheet activities of teachers and students and learning outcomes. This thesis presents the increase in the number of students who reached the KKM of 6 people (37.50%) at the base score to 13 people (81.25%) in the first cycle and increased to 14 people (87.50%) in the second cycle. This means that have been completed in the classical style. An increase in the average learning outcomes of the basic score is 64.38 into 75.00 in the first cycle and 83.44 in the second cycle. An increase in teacher activity. At the first meeting of the first cycle of the percentage of activity the teachers are 58.33%, 70.83% the second meeting. While the second cycle of the first meeting with a percentage of 87.50%, and the second meeting increased 91.67%. While student activity also increased that the first meeting of the first cycle of the percentage of student activity is 54.17%, 66.67% the second meeting, the first meeting of the second cycle of 79.17% and a meeting with an average of 87.50%. The results of the study in the fourth grade primary school 007 Java Chart District of Bangko prove that the implementation of cooperative learning model TSTS can improve student learning outcomes IPS Class IV Elementary School District of Bangko 007 Bagan Jawa. Key words: Cooperative Type Two Stay Two Stray, learning outcomes IPS